Application of Active Learning Methods in Overcoming Student Boredom at SD Negeri 094175 Margosono - Damayanti, Asri (Jurnal Cendekia Islam Indonesia, 2025)
Islamic Religious Education (PAI) learning often faces challenges in the form of student boredom in class, which has an impact on low participation and understanding of the material. This study aims to analyze the application of active learning methods in overcoming student boredom at SD Negeri 094175 Margosono. The method used in this study is a qualitative approach with observation, interview, and documentation techniques. The results of the study indicate that the application of active learning methods, such as group discussions, educational games, and role-playing, can increase students' interest in learning. Students become more enthusiastic, actively participate, and understand the material being taught more easily. In addition, teachers play an important role in creating an interactive and enjoyable learning atmosphere by implementing various learning strategies. The obstacles faced in implementing this method include time constraints, lack of supporting learning media, and differences in student learning abilities. However, with good classroom management and the selection of appropriate methods, student boredom can be minimized. Therefore, active learning methods can be an alternative for teachers in creating a more effective and enjoyable learning process.